Pelatihan Asertivitas untuk Memperkuat Self Confidence pada Mahasiswa di Yogyakarta - Wenty Lestari; Kamsih Astuti; Novia Sinta Rochwidowati (LPPM Universitas Proklamasi 45, 2020)
The study aims to examine the influence of assertiveness training toward increasing self confidence in college students woman dormitories